MODEL OF TRANSFORMATION TO GREEN HYDROGEN ECONOMY IN EMERGING COUNTRIES - Banerjee, Barunava (Digital Repository of Theses - SSBM Geneva, 2022)
1.1 Introduction Green hydrogen holds significant promise in meeting our planet’s energy demands. This research paper searches for avenues and will offer a model of making the green –hydrogen transformation in the emerging countries of Asia, Europe and Africa, economically viable, less costly, environment friendly and lead to a contributor to a more sustainable economy. 1.2 Objective 1.2.1 This research paper will offer a model of making the green –hydrogen transformation in the emerging countries of Asia, Europe and Africa, less costly and environment friendly. 1.2.2 This research paper will also explore and suggest necessary steps to be taken so that green hydrogen contributes to 25% of the total world economy by 2035. 1.3 Methodology 1.3.1 Critical analysis of the literature review papers on the subject was undertaken, to draw conclusions on what more needs to be done to achieve a Green Hydrogen Economy of about 25% of the world economy by 2035, in the emerging countries. 1.3.2 Based on the feedback on the questionnaire, a statistical model has been projected to suggest the requirements based on the following five parameters: Cost of production, Expenditure / Investments, Innovation on tech expansion, Time and Stakeholders (private, public) participation viii 1.4 Conclusions and Results 1.4.1 The responses from 75 persons on the questionnaire, supports our findings from our research model and our conviction that a “Green Hydrogen Economy is possible by 2035” is confirmed. The cost reduction to about USD 2 per Kg by 2035, predicted by our model is also supported by the survey. 1.4.2 For emerging nations of Asia, Africa & Europe to have a 25% contribution from green hydrogen of their total energy requirements, they would spend about USD 500-600 billion on green hydrogen and other renewable energies during 2030-2040. Support from developed countries in this matter is also a must. 1.4.3 The survey also supports that a larger public-private participation is required in all the emerging nations, to contribute to enhanced production of electrolyzers and for funding of a larger infrastructure to enable green hydrogen production , storage and transportation